Alpha defensin, leukocyte esterase, C-reactive protein, and leukocyte count in synovial fluid for pre-operative diagnosis of periprosthetic infection. (October 2018) - De Vecchi, Elena; Romanò, Carlo Luca; De Grandi, Roberta; Cappelletti, Laura; Villa, Francesca; Drago, Lorenzo
Synovial fluid analysis for diagnosis of prosthetic joint infections has gained increasing interest in the recent past when markers more specific for these infections than the serum ones have been identified. Despite the important steps forward, identification of a gold standard has not yet been identified. In this study, usefulness of alpha defensin, leukocyte esterase, C-reactive protein (CRP), and white blood cells (WBCs) in synovial fluids alone and in combination for diagnosis of prosthetic joint infection was evaluated. Synovial fluids from 32 infected and 34 not infected patients were analyzed. Sensitivity, specificity, positive and negative predictive values, diagnostic accuracy, and receiver-operating characteristic (ROC) curves were calculated for each parameter. Moreover, combination of coupled variables was also evaluated by logistic regression analysis. Sensitivity of alpha defensin, CRP, leukocyte count, and leukocyte esterase were 84.4%, 87.5%, 93.7%, and 93.8%, respectively. Specificity was 91.2% for leukocyte counts, 94.1% for alpha defensin, 97.0% for CRP, and 97.1% for leukocyte esterase. Diagnostic accuracy was 89.4% for alpha defensin, 92.4% for WBC counts and CRP, and 95.5% for leukocyte esterase. No statistical differences were observed in area under the curve (AUC) of the ROC curves of alpha defensin, CRP, and leukocyte counts. Logistic regression analysis applied to a model comprising all the variables showed an AUC higher than AUC of coupled variables. In conclusion, results of this study confirm the high sensitivity and specificity of synovial leukocyte esterase for diagnosis of prosthetic joint infection, also suggesting the need to assess a panel of markers to optimize diagnosis of these infections.